2018
DOI: 10.5195/ijt.2018.6249
|View full text |Cite
|
Sign up to set email alerts
|

Clinicians' Perspectives of a Novel Home-based Multidisciplinary Telehealth Service for Patients with Chronic Spinal Pain

Abstract: Chronic spinal pain conditions can often be successfully managed by a non-surgical, multidisciplinary approach, however many individuals are unable to access such specialised services within their local community. A possible solution may be the delivery of care via telerehabilitation. This study aimed to evaluate clinicians’ perspectives on providing clinical care via telerehabilitation during the early implementation of a novel spinal telerehabilitation service. Eight clinicians’ were recruited, completing su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
71
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 26 publications
8
71
0
1
Order By: Relevance
“…The observation that desire to continue offering telemedicine visits after the COVID-19 pandemic correlates not only with confidence with the examination and satisfaction with the modality, 22 but also with personal factors such as belief that adaptability is an important element of being a clinician, clinicians who identify as being more perceiving (value flexibility) than judging (value organization), and less preference for in-person work meetings over virtual meetings suggests that clinicians who are going to have less preference for telemedicine going forward can be identified by other traits and preferences. In the qualitative interviews along with our personal observations and interactions, including prior investigations, 23,24 we found that both clinicians and patient concerns about telemedicine are things that lessen after a good telemedicine experience. The pandemic has provided many more clinicians and patients with good telemedicine experiences and the likelihood of continued use is high.…”
Section: Discussionmentioning
confidence: 77%
“…The observation that desire to continue offering telemedicine visits after the COVID-19 pandemic correlates not only with confidence with the examination and satisfaction with the modality, 22 but also with personal factors such as belief that adaptability is an important element of being a clinician, clinicians who identify as being more perceiving (value flexibility) than judging (value organization), and less preference for in-person work meetings over virtual meetings suggests that clinicians who are going to have less preference for telemedicine going forward can be identified by other traits and preferences. In the qualitative interviews along with our personal observations and interactions, including prior investigations, 23,24 we found that both clinicians and patient concerns about telemedicine are things that lessen after a good telemedicine experience. The pandemic has provided many more clinicians and patients with good telemedicine experiences and the likelihood of continued use is high.…”
Section: Discussionmentioning
confidence: 77%
“…The lower rating is somewhat in contrast to the growing emphasis on the use of technologies and media that may range from simple SMS appointment reminders in use for well over a decade (Boksmati, Butler‐Henderson, Anderson, & Sahama, ; Car, Ng, Atun, & Card, ), to more sophisticated wearable devices to track health information (e.g. physical activity, heart rate) (Haghi, Thurow, & Stoll, ), to the use of telehealth providing management from remote sites to those who otherwise may not have been able to access care (Cottrell, Galea, O'Leary, Hill, & Russell, , Cottrell et al, , Cottrell et al, ). It will certainly be interesting to evaluate the perceived importance of this attribute to patient uptake in the future when these forms of technology are more mainstream.…”
Section: Discussionmentioning
confidence: 97%
“…Real-time telerehabilitation appears to be effective and comparable to conventional methods of healthcare delivery for the improvement of physical function and pain in a variety of musculoskeletal conditions. 24 It has already been reported in the areas of spine pain, chronic pain, and a variety of musculoskeletal disorders, 38,[42][43][44][45][46][47] which are common in chiropractic practice. Telehealth has enabled us to maintain continuity of care with our patients and we plan on further enabling RTVC as a valuable tool.…”
Section: T a G G E D H 1 Considerations For The Futuret A G G E D E N Dmentioning
confidence: 99%